Role of genetic variation in Toll like receptor-5 with rheumatoid arthritis pathogenicity in Iraqi patient: TLR-5 Variation & RA Pathogenicity in iraq - Khauon, Aliaa; Ali Hussein Alwan; Saad L. Hamed (Iraqi Journal of Cancer and Medical Genetics, 2023)
Background: Rheumatoid Arthritis (RA) is a persistent inflammatory condition characterized by the immune system’s improper attack of bodily tissues. Rheumatoid arthritis is a chronic autoimmune disorder that impacts the synovial membrane of joints, leading to an inflammatory response characterized by painful swelling. Over time, this condition can progress to the erosion of bone tissue and the development of joint deformities. Aim: characterized the primary objective of the present study was to evaluate the impact of certain variations in the TLR5 gene (namely, rs2072493 and rs45508499) on the severity of Rheumatoid Arthritis among patients from Iraq. Materials and methods: Approximately similar samples from apparently healthy individuals are enrolled as control. The patients attended from April to June 2022 at the Baghdad teaching hospital / medical city /Baghdad / Iraq. It was based on a clinical examination . The single nucleotide polymorphisms (rs2072493 T/A, C, and rs45508499A/G) are examined using the Tetra ARAMS technique. All (SNPs) from the control person are analyzed in the Chi-square test. Results: The analysis revealed a significant association between the rs45508499 polymorphism and the trait of interest. However, no significant association was observed for the rs2072493 polymorphism. Conclusion: The current investigation showed that the presence of TLR5 polymorphism at rs4550899 was associated with RA but rs2072493 was not associated with any effect on the susceptibility to Rheumatoid arthritis .